The identity of Osteobrama cotio, and the status of “Osteobrama serrata” (Teleostei: Cyprinidae: Cyprininae) - Rahman, Md. Mizanur; Norén, Michael; Mollah, Abdur Rob; Kullander, Sven (Zootaxa, 2018)
Osteobrama cotio is considered to be a widespread species in India and Bangladesh. Mitochondrial DNA (COI, 16S rRNA) shows that populations from the Meghna River, Karnafuli and Sangu Rivers, Narmada River, and Godavari River are genetically distinct from each other. No morphological differences were found to separate Meghna and Karnafuli+Sangu populations, however. A putative new species, “Osteobrama serrata” has been described from the Barak River basin, stated to be distinguished from O. cotio by the presence of a serrated third dorsal-fin ray. The description of “O. serrata” does not fulfil requirements of the International Code of Zoological Nomenclature, (International Commission on Zoological Nomenclature 1999) and the name is thus unavailable. Published DNA sequences of “Osteobrama serrata” are identical to sequences of O. cotio from Bangladesh. As mentioned already in the original description, O. cotio has a serrated third dorsal-fin ray.